Collective efficacy interdisciplinary perspectives on international leadership - Normore, Anthony H.; Erbe, Nancy (Advances in educational administration ;, 2013)
Drawing from the works of renowned psychologist, Albert Bandura, an interdisciplinary and international group of collaborative and well-respected scholars demonstrate the positive impact of collective efficacy on an international scale. Bandura stated that "A group's attainments are the product not only of shared knowledge and skills of the different members, but also of the interactive, coordinative, and synergistic dynamics of their transactions" (Bandura, 2006, p. 316). In this book leaders from many professional disciplines and global cultures collectively shared research, understanding, and experiences about leadership development and growth. Disciplines include education, law, sociology, theology, psychology, law enforcement, aviation, corrections, criminal justice, military, peace and negotiation. Authors represent North America, Latin America, Asia, Middle East, Europe, and Africa. This book exemplifies the benefits of collective efficacy and bridging gaps among professions and scholars where there's often a tendency to work in silos and isolation. We share much that might benefit us and others when explored and discovered. Emergent themes include transformational leadership, servant leadership, service learning and community development, consciousness and emotional intelligence, leaders of the new millennium, and challenges for future collective efficacy.